2004
DOI: 10.1111/j.0014-2956.2004.04242.x
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipase C, protein kinase C, Ca2+/calmodulin‐dependent protein kinase II, and redox state are involved in epigallocatechin gallate‐induced phospholipase D activation in human astroglioma cells

Abstract: We show that epigallocatechin-3 gallate (EGCG), a major component of green tea, stimulates phospholipase D (PLD) activity in U87 human astroglioma cells. EGCG-induced PLD activation was abolished by the phospholipase C (PLC) inhibitor and a lipase inactive PLC-c1 mutant, which is dependent on intracellular or extracellular Ca

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 41 publications
1
21
1
Order By: Relevance
“…PKC ␣ is a well-established neuron cell survival factor participating also in cell growth and differentiation [63,64] . In support, a recent report shows that treatment of human cells with EGCG induces a specifi c translocation of PKC ␣ to the membrane [65] .…”
Section: Mechanism Of Neuroprotection By Green Tea Catechinssupporting
confidence: 62%
“…PKC ␣ is a well-established neuron cell survival factor participating also in cell growth and differentiation [63,64] . In support, a recent report shows that treatment of human cells with EGCG induces a specifi c translocation of PKC ␣ to the membrane [65] .…”
Section: Mechanism Of Neuroprotection By Green Tea Catechinssupporting
confidence: 62%
“…Several studies suggest that PLC␥1 regulates PLD activity in intracellular signal transduction (42,53,54). Thus, we tried to determine whether PLC␥ signaling pathway is involved in Der f 2-induced PLD activation and found that pretreatment with U73122 or PAO, specific PLC␥ inhibitors, completely blocked Der f 2-induced PLD1 activation and IL-13 production in BEAS-2B cells, suggesting that PLC␥ activation is related to PLD activation and IL-13 production.…”
Section: Discussionmentioning
confidence: 99%
“…To investigate how Der f 2 activates PLD1, we examined PLC␥ signaling because there are studies suggesting that PLC␥ activation results in increased PLD activity (42). The mammalian PLC␥ family has two closely related members, PLC␥1 and PLC␥2.…”
Section: Der F 2-induced Il-13 Production and Expression Are Regulatementioning
confidence: 99%
“…It has been found that PI-PLC activation results in the generation of diacylglycerol (DAG) and inositol 1, 4, 5-triphosphate which activates protein kinase C (PKC) and mobilizes Ca 2þ , respectively [Kim et al, 2004]. We have already demonstrated that PKC is not involved in hippocalcin-induced PLD2 expression pathway.…”
Section: Discussionmentioning
confidence: 99%
“…There have been a few reports suggesting that some of the intracellular LPA actions require the PLD signaling via protein kinase C (PKC) [Gustavsson et al, 1994;Kim et al, 2004]. To determine whether PKC is involved in hippocalcin-induced PLD2 expression potentiated by LPA, we examined the effect of PKC downregulation on hippocalcin-induced PLD2 expression potentiated by LPA.…”
Section: Pkc Is Not Involved In the Hippocalcin-induced Pld2 Expressionmentioning
confidence: 99%